AKT3 drives adenoid cystic carcinoma development in salivary glands. (28th December 2017) - Zboray, Katalin; Mohrherr, Julian; Stiedl, Patricia; Pranz, Klemens; Wandruszka, Laura; Grabner, Beatrice; Eferl, Robert; Moriggl, Richard; Stoiber, Dagmar; Sakamoto, Kazuhito; Wagner, Kay‐Uwe; Popper, Helmut; et al.
Abstract: Salivary gland cancer is an aggressive and painful cancer, but a rare tumor type accounting for only ~0.5% of cancer cases. Tumors of the salivary gland exhibit heterogeneous histologic and genetic features and they are subdivided into different subtypes, with adenoid cystic carcinomas (ACC) being one of the most abundant. Treatment of ACC patients is afflicted by high recurrence rates, the high potential of the tumors to metastasize, as well as the poor response of ACC to chemotherapy. A prerequisite for the development of targeted therapies is insightful genetic information for driver core cancer pathways. Here, we developed a transgenic mouse model toward establishment of a preclinical model. There is currently no available mouse model for adenoid cystic carcinomas as a rare disease entity to serve as a test system to block salivary gland tumors with targeted therapy. Based on tumor genomic data of ACC patients, a key role for the activation of the PI3K‐AKT‐mTOR pathway was suggested in tumors of secretory glands. Therefore, we investigated the role of Akt3 expression in tumorigenesis and report that Akt3 overexpression results in ACC of salivary glands with 100% penetrance, while abrogation of transgenic Akt3 expression could revert the phenotype. In summary, our findings validate a novel mouse model to study ACC and highlight the druggable potential of AKT3 in the treatment of salivary gland patients. Abstract : AKT3 expression is associated with bad prognosis in head and neck cancer. Taking advantage of a novel mouse model, we report that conditional Akt3 overexpression triggers adenoid cystic carcinomas in the salivary glands of mice with 100% penetrance. We further show that these adenoid cystic carcinomas are completely dependent on expression of the oncogene.